Bony Fishes from the Late Miocene and Pliocene Strata of Popovo Locality (Ukraine): Taxonomic Changes and Their Palaeoecological Explanation - Kovalchuk, O M (Zoodiversity (Online), 2014)
Bony Fishes from the Late Miocene and Pliocene Strata of Popovo Locality (Ukraine): Taxonomic Changes and Their Palaeoecological Explanation. Kovalchuk, O. M. - Th e present paper deals with results of studying of the fossil fish remnants from the Late Miocene and Pliocene strata of Popovo locality (Southern Ukraine). Our aim was to show local taxonomic changes in freshwater fish communities through-out the specified range of geological time. Twenty seven species of the 20 genera, 6 families (Cyprinidae, Cobitidae, Siluridae, Salmonidae, Esocidae, Percidae) and 5 orders (Cypriniformes, Siluriformes, Salmoniformes, Esociformes, Perciformes) were identified from the 4 heterochronous bonyferous layers. Basing on taxonomic richness, diversity, complexity and similarity of communities, it can be assumed, that changes in their qualitative and quantitative composition were caused by hydrological regime transformation, palaeogeographical alterations and also local taphonomic features.